2019
DOI: 10.1136/bcr-2019-231464
|View full text |Cite
|
Sign up to set email alerts
|

Development of pyogenic granuloma with strong vascular endothelial growth factor receptor-2 expression during ramucirumab treatment

Abstract: The angiogenesis inhibitor ramucirumab (IMC-1121B) is a fully humanised IgG1 monoclonal antibody targeting the extracellular domain of vascular endothelial growth factor receptor 2. Ramucirumab has been approved as a second-line treatment for lung cancer. Pyogenic granuloma is an acquired, benign vascular tumour of the skin or mucous membrane. We encountered a patient with pyogenic granuloma who was treated with ramucirumab. The patient was a 48-year-old Japanese woman with advanced lung cancer who had been he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This paradoxical angiogenic event during ramucirumab therapy was noted in subsequent case reports, albeit with other combined oncologic therapies such as paclitaxel and docetaxel [4,7,9,10]. The timing of the tumor onset ranged from approximately two weeks to six months after administration with multiple sites affected including the mucosa, nail apparatus, trunk, and extremities [4,7,9,10]. While vascular endothelial growth factor inhibition is thought to downregulate the tumoral angiogenesis, the mechanism behind this paradoxical reaction remains largely undefined.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This paradoxical angiogenic event during ramucirumab therapy was noted in subsequent case reports, albeit with other combined oncologic therapies such as paclitaxel and docetaxel [4,7,9,10]. The timing of the tumor onset ranged from approximately two weeks to six months after administration with multiple sites affected including the mucosa, nail apparatus, trunk, and extremities [4,7,9,10]. While vascular endothelial growth factor inhibition is thought to downregulate the tumoral angiogenesis, the mechanism behind this paradoxical reaction remains largely undefined.…”
Section: Discussionmentioning
confidence: 85%
“…Multiple causative agents have been implicated in the pathogenesis including chronic irritation, prior trauma, hormones, and systemic medications such as retinoids, indinavir, and epidermal growth factor receptor inhibitors [ 2 ]. We report a case of eruptive pyogenic granulomas as a proposed synergistic effect of two systemic medications known to cause these vascular tumors: epidermal growth factor receptor inhibitors and vascular endothelial growth factor receptor inhibitors [ 3 , 4 ]. To our knowledge this is the first documented case in the literature highlighting the combined synergy between these two oncologic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Unique dermatologic toxicities of ramucirumab include vascular tumors such as cherry angioma/hemangioma 38,39,277 and lobular capillary hemangioma (pyogenic granuloma) 38,68–71,278 . Notably, investigators have found the p.T771R kinase‐domain mutation of the KDR gene encoding for VEGFR2, known to be associated with human angiosarcomas, 279 in vascular tumors arising from ramucirumab exposure 70,280 . Table 2 lists the types of dermatologic toxicities seen with mAbs targeting VEGF/VEGFR2, including reports of the clinical aspects of dermatologic toxicities to those listed 47,48 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there are several reports on PGs and hemangiomas occurring in patients receiving ramucirumab. Lim et al first reported the development of an angioma during the administration of ramucirumab in 2015 (5); several cases have been reported since then, including sporadic and multiple occurrences (6)(7)(8); tumors appeared at a minimum of two months and a maximum of six months after starting ramucirumab (6)(7)(8). The pathogenesis of ramucirumabrelated PG remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of ramucirumabrelated PG remains unknown. Ibe et al reported on a case of PG of the fingers, where strongly positive immunostaining was observed for VEGFR2; they hypothesized that following ramucirumab administration, a small wound triggered VEGFR2 overexpression owing to a mutation in KDR (p.T771R), which is a driver of vascular lesions (6).…”
Section: Discussionmentioning
confidence: 99%